Financing Infrastructure Projects through Public–Private Partnerships in India. Issue 1 (January 2014) - Ramakrishnan, T. S.
India has been suffering from a huge deficit in infrastructure facilities. The Indian government perceives the public–private partnership (PPP) model as the preferred mode to bridge this deficit and has initiated several measures in that regard. This paper discusses the basic aspects of PPP and how it works in India. Financing for infrastructure is one of the major issues. This paper explains various issues such as over-dependence on commercial banks for debts; inadequate financing from infrastructure finance companies; issues in external commercial borrowing; nonavailability of mezzanine financing; partial availability of insurance, pension, and provident funds; and nonfinancing issues that are plaguing infrastructure finance in India. The recent improvements such as infrastructure debt bonds, relaxed norms for external commercial borrowing, and reasonable exit options are also examined. The paper suggests various financial reforms that are needed for PPP financing in India such as tapping into savings, allowing foreign direct investment, increasing the cap on viability gap funding, allowing balloon payments, giving impetus for corporation bonds, and building infrastructure corpus.